“HEY, I LIKE YOUR VIDEOS. RELATE MUCH!”LOCATING SISTERHOOD IN A POSTCOLONIAL PUBLIC ON YOUTUBE - Cabalquinto, Earvin Charles Borja; Soriano, Cheryll (AoIR Selected Papers of Internet Research, 2019)
As part of a broader project that seeks to investigate the brokering of digitally-mediated intimacies through matchmaking platforms and social media channels, this paper unpacks the formation of ‘online sisterhood’ in a postcolonial intimate public, as evinced in the comments of viewers on selected YouTube videos of Rhaze, a Filipina YouTuber who is married to an Australian man. With a massive following of over 450 thousand followers, Rhaze’s videos typically receive diverse comments from her viewers and subscribers. This exposition is facilitated by collecting, categorising and analysing selected comments from Rhaze’s top videos. The comments were analysed through discourse analysis, paying special attention to the factors that influence digital media practices. The findings reveal that competing comments are shaped by postcolonial views on a gendered, racialized and class-based body in an interracial relationship. We then coin the term ‘online sisterhood’, reflecting the shared support that women nurture with other women through online practices. Ultimately, online sisterhood displays how Filipino women married to a white foreign national generate and negotiate spaces of mutual support in a neoliberal state. Paradoxically, a neoliberal government benefits from such cross-border and mediated mobility of Filipina migrants through the commodification of their everyday life. It is through this point that we argue for a closer evaluation of the role of ‘online sisterhoods’ in the construction of female subjectivity and imaginaries of mobility in the Global South.